Modeling the Load Pattern of a Network of Buildings with Installed Load Manage-ment Devices using Matlab/Simulink. - Iffat Hasnain (2008)
This thesis focuses on the design, modeling and implementation of system that can simulate the resulting load profile for any required day, season etc; by using the de-tailed device parameters of building(s) in network(s) i.e. valid working time, minimum run & maximum shut down times etc, and compare the results with power consump-tion data, while being synchronized with the load management system at the same time. In this regard a work forecast algorithm was designeddeveloped which can cal-culate the possible reduction in power by turning off the devices in the remaining quarter of an hour during their valid working times; by keeping the track of device pa-rameters, hence providing the detailed information that which devices could be turned on or off and for how long. Implementation & Validation of work is done in Mat-lab/Simulink.